2015
DOI: 10.1111/den.12498
|View full text |Cite
|
Sign up to set email alerts
|

Recent clinical management of antithrombotic agents for gastrointestinal endoscopy after revision of guidelines in Japan

Abstract: In 2012, the Japan Gastroenterological Endoscopy Society (JGES) revised guidelines for the management of gastrointestinal endoscopy for patients using antithrombotic agents. The conventional guidelines emphasized reducing the bleeding risk that accompanies gastrointestinal endoscopy, but the present guidelines prioritize reduction of thromboembolism risk during discontinuation of antithrombotic agents, which is consistent with Western guidelines. When the advantages outweigh the disadvantages, the guidelines p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 33 publications
(28 reference statements)
0
14
0
2
Order By: Relevance
“…Guidelines from the Japan Gastroenterological Endoscopy Society 74 stipulate that low-bleeding-risk procedures can be performed without discontinuation of all types of antithrom- botic agents, although procedures with a high bleeding risk should be carried out with discontinuation of antithrombotic agents. The guidelines also recommend substituting heparin bridging for warfarin or DOACs for these procedures, although the efficacy of bridging therapy is controversial, as Ono et al reported that heparin bridging therapy increased the bleeding rates to approximately 20%.…”
Section: Current Att Management In the Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines from the Japan Gastroenterological Endoscopy Society 74 stipulate that low-bleeding-risk procedures can be performed without discontinuation of all types of antithrom- botic agents, although procedures with a high bleeding risk should be carried out with discontinuation of antithrombotic agents. The guidelines also recommend substituting heparin bridging for warfarin or DOACs for these procedures, although the efficacy of bridging therapy is controversial, as Ono et al reported that heparin bridging therapy increased the bleeding rates to approximately 20%.…”
Section: Current Att Management In the Guidelinesmentioning
confidence: 99%
“…The guidelines also recommend substituting heparin bridging for warfarin or DOACs for these procedures, although the efficacy of bridging therapy is controversial, as Ono et al reported that heparin bridging therapy increased the bleeding rates to approximately 20%. 74 Further accumulation of evidence concerning the management of NOACs is required. 74 EST and EUS-GBD are also classified as high-bleedingrisk procedures, 74 and are allowed without discontinuation of aspirin monotherapy only in patients with a high risk of thromboembolism.…”
Section: Current Att Management In the Guidelinesmentioning
confidence: 99%
“…Pasien yang memerlukan terapi dual antiplatelet sebaiknya tetap melanjutkan penggunaan aspirin, dan keputusan untuk menghentikan thienopyridine sebaiknya dikonsultasikan dengan ahli kardiologi. 3,5,12 Berdasarkan pedoman Japan Gastroenterogical Endoscopy Society, pada pasien yang mendapatkan novel oral anticoagulant, pemberian dapat dilanjutkan atau dikurangi dosisnya pada pagi hari jika akan dilakukan prosedur dengan risiko perdarahan yang rendah. Sedangkan, pada prosedur dengan risiko perdarahan yang tinggi, pemberian dapat ditunda 24-48 jam sebelum tindakan, tergantung dengan jenis agen yang dipakai.…”
Section: Stratifikasi Risiko Terjadinya Kejadian Tromboemboliunclassified
“…Apabila terdapat kelainan eliminasi obat, maka penghentian pemberian dapat dilakukan lebih lama. 7,12…”
Section: Stratifikasi Risiko Terjadinya Kejadian Tromboemboliunclassified
“…Thus, accumulation of evidence to validate the recommendations in the guidelines became easier than before. Nowadays, the acceptance of biopsy and high‐bleeding‐risk procedures without cessation of any antithrombotics and aspirin are growing, respectively …”
mentioning
confidence: 99%